Hop-off hop-on: Assimilates on the road - Stadler, Ruth (Journal of plant physiology, 2021)
Solutes are subject of constant release and retrieval processes during long distance transport in higher plants. In the stem, sugars and amino acids are used for storage or for nutrition of parenchymatic tissues. Modification of export/import capacities along the transport phloem might provide a powerful tool to enhance the productivity of crop plants.